Effect of atmospheric pressure plasma jet on the structure and physicochemical properties of wheat starch - Ji, Hongfang; Li, Dandan; Zhang, Lingwen; Li, Manjie; Ma, Hanjun (Frontiers in Nutrition, 2024)
The effect of atmospheric pressure plasma jet (APPJ) with different discharge power (0, 400, 600, 800 W) on the structure and physicochemical properties of wheat starch were evaluated in this study. After APPJ treatments, significant declines in peak viscosity, breakdown viscosity, and final viscosity of wheat starch pasting parameters were observed with increase of plasma treatment power. Being treated with discharge power of 800W, the PV and BD value of wheat starch paste significantly dropped to 2578 and 331 cP, respectively. Apparently, APPJ could raise the solubility of wheat starch, while reduce the swelling capacity, and also lower the G' and G'' value of wheat starch gel. Roughness and apparent scratch was observed on the surface of the treated wheat starch granules. Although APPJ treatment did not alter wheat starch's crystallization type, it abated the relative crystallinity. APPJ treatment might be useful in producing modified wheat starch with lower viscosity and higher solubility.